The effectiveness of the incentive autonomous learning strategies (IALS) module to improve chinese non-english major undergraduates’ EFL speaking proficiency - Asmaa AlSaqqaf; Yi Yang; Ke Hu (Academy publication, 2024)
Very limited research has examined the application of the Incentive Autonomous Learning Strategies (IALS) module to improve the speaking proficiency of English as a foreign language (EFL) among Chinese non-English major undergraduates at a public university in China. Thus, this study attempted to bridge this gap by incorporating autonomous learning with incentive strategies to enhance Chinese non-English major undergraduates’ EFL oral performance. Utilising a quantitative research approach, this study adopted a quasi-experimental design to carry out a 14-week intervention. The participants were purposively sampled with the experimental group undergoing the IALS speaking intervention, while the control group received conventional in-situ teaching approaches. A pretest and post-test were conducted on both groups to examine any changes in their speaking proficiency before and after the intervention. Results obtained from the paired-sample t-test demonstrate a statistically significant increase in the experimental group’s EFL oral performance, rising from a mean score of 50.52 before the intervention to 71.60 after the intervention. The control group’s mean score also improved from a pretest mean score of 51.08 to a mean score of 54.98 in the posttest. These results suggest that the IALS module has proven to be efficacious in improving Chinese non-English major undergraduates’ EFL speaking proficiency. It is hoped that the results of this study might provide insights into the effective strategies to enhance English speaking skills among Chinese non-English major undergraduates in EFL contexts.